Prevalence of shigellosis and associated risk factors among undergraduate students of a private university in Ogun State, Nigeria - Seyi Samson Enitan; Joan Odigie; Oluyemisi Ajike Adekunbi; Okondu Ogechukwu Emmanuel; Nwachi Idume Ogbonna; Tsague Metago Claudette Laura; Chukwudi Amaechi Ofodile; Grace Eleojo Itodo; Marcel Edafetanure-Ibeh; Abiodun Oluwasegun Adetola (School of Medicine, Universitas Syiah Kuala, 2021)
This cross-sectional, institutional-based study aimed to determine the prevalence of shigellosis and associated risk factors among Babcock University students in Ogun State, Nigeria. One hundred and twenty (120) undergraduate students, 80 females and 40 males, were asked to provide stool specimen in a sterile leak-proof single-use universal bottle with a screw-capped lid. Standard microbiological techniques were used to analyse the stool samples. A questionnaire was designed to collect demographic and clinical information from participants. The data obtained were statistically analysed using the SPSS Statistics software (version 18.0). The study showed that there was no occurrence of shigellosis among the study participants (0%), but other enteric pathogens infection were present in all participants (100%). The three most common mono-infections found among the study participants included Staphylococcus aureus (40%), followed by Escherichia coli (16.7%), and Salmonella typhi and Bacillus spp. (3.3%, each). While the most common prevalence of dual-infections included Staphylococcus aureus and Escherichia coli (33.3%), followed by Staphylococcus aureus and Salmonella typhi (3.3%). The proportion of participants who were asymptomatic (66.7%) was significantly higher than the symptomatic ones (33.3%). Identified risk factors of non-Shigella enteric infection included consumption of beef, vegetables, fruits, poultry/poultry products, as well as street foods, poor hand hygiene before eating, anal cleaning, and poor hand hygiene after toileting. Although shigellosis did not exist among undergraduate students of Babcock University, this study highlighted the existence of other enteric infections among the study participants. Therefore, the necessary preventive measures should be ensured and sustained.